2014
DOI: 10.1111/ijac.12307
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mechanical Behavior of Magnesia Spinel Refractories Using Image Correlation

Abstract: International audienceThe improvement in thermal shock resistance of refractory materials is among the crucial properties that interest researchers and industrials. The "flexibility" in terms of large strain-to-rupture is, up to now, an important parameter to develop such characteristic. This can be obtained by generating a network of microcracks within the microstructure of the material under mechanical solicitations. As an outcome, the mechanical behavior can vary from fragile to a large nonlinear one depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…For each subset, a correlation function is used to estimate the degree of similarity between the reference image state and the current one (for each given load) [31].…”
Section: Digital Correlationmentioning
confidence: 99%
“…For each subset, a correlation function is used to estimate the degree of similarity between the reference image state and the current one (for each given load) [31].…”
Section: Digital Correlationmentioning
confidence: 99%
“…Several studies have reported the thermal shock resistance and slag resistance of aluminamagnesia castables. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Additives such as TiO 2 , 6,7 SiO 2 , 8-10 and ZrO 2 11 have been introduced into alumina-magnesia castables to improve their performance. The effect of spinel composition on the slag resistance of alumina-spinel and alumina-magnesia castables was investigated by Ko,13,14 who found that the extent of penetration of slag into the prepared castables decreased with increasing MgO content in the spinels.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina–magnesia castables have been considered potential replacements to alumina–chrome castables. Several studies have reported the thermal shock resistance and slag resistance of alumina–magnesia castables . Additives such as TiO 2 , SiO 2 , and ZrO 2 have been introduced into alumina–magnesia castables to improve their performance.…”
Section: Introductionmentioning
confidence: 99%